Efek Kombinasi Musik Gamelan Gong Kebyar dan Cahaya LED (Light Emitting Diode) Terhadap Pertumbuhan dan Produktivitas Sawi Pakcoy (Brassica rapa L.) - Sigmarawan, Gede Teguh; Wijaya, I Made Anom S.; Budisanjaya, I Putu Gede (Jurnal BETA (Biosistem dan Teknik Pertanian); Vol 8 No 1 (2020): AprilDO - 10.24843/JBETA.2020.v08.i01.p01, 2019)
This study aims to (1) determine the effect of the combination of gong kebyar gamelan music and LED light on the growth and productivity of pakcoy mustard and (2) determine the combination of gong kebyar gamelan music and LED light that provides the best growth and productivity in pakcoy mustard plants. This study used pakcoy mustard plants which are given a treatment of the combination of gong kebyar gamelan music and different LED light. The first treatment used a combination of gong kebyar gamelan music and white LED light, treatment 2 used a combination of gong kebyar gamelan music and red blue LED light, and treatment 3 used a combination of gong kebyar gamelan music and blue red and white LED light. The data obtained were analyzed using one way anova test and followed by Duncan test with a confidence level of 95%. The variables observed were plant height, canopy area, leaf greenness, root length, wet weight and dry weight of plant shoots and roots. The results showed that giving a combination of gong kebyar gamelan music and LED light had a significant effect on the growth and productivity of pakcoy mustard. The combination of gong kebyar gamelan music and red blue LED light gave the best growth and productivity, with plant height, canopy area, leaf greenery, root length, shoot wet weight, root wet weight, shoot dry weight and root dry weight, respectively also included 27,176 cm, 1457.59cm2, 160.03, 23.6cm, 91.68g, 4.63g, 5.26g, 4.63g and 0.42g.